Cyber Porn (Crime without Victim) in the country of Indonesia - Siti Faridah (Universitas Janabadra, 2018)
The number of pornography in Indonesia increase from year to year. Data from National Commission for Child Protection (KPAI) in 2016 there are 587 cases of pornography crimes. Law No. 44 of 2008 concerning pornography (pornography act), Law No. 11 of 2008 concerning Electronic Information and Technology (ITE Act) not maximally ensnare the perpetrators of crime. The victims of this crime are also widespread in all circles even to children. In fact, in many cases the position of the perpetrator is also a victim. This paper will examine two important points: how cyber porn reviews in psychiatric studies, and how to protect victims of cyber porn crime in Indonesia. This paper highlights that the crime of cyber porn in legislation in Indonesia still has many weaknesses, especially related between victim and perpetrator of this crime. Furthermore, this paper asserts that the importance of victim protection for cyber porn in Indonesia. Keywords :cyber porn, victimology, victim and pornography